Energy structure change and carbon emission trends in China. (15th November 2016) - Wang, Zheng; Zhu, Yanshuo; Zhu, Yongbin; Shi, Ying
Abstract: This article builds a hybrid energy model based on energy demand and energy supply equilibrium, along with the objective of minimizing costs. To estimate the differences between various energy technologies that impact the economy, efficiency and carbon emissions, we simulated the structure of China's future energy roadmap and trends of carbon emissions. The simulation results show that if international oil prices decline and China's economic growth appropriately deviates from the golden growth, carbon emissions can reach a peak in 2025, relying mainly on nuclear energy to substitute for coal. In other words, the peak of carbon emissions in China can technically be achieved by 2025, but certain economic losses will occur. With the objective of costs minimization, the results indicate that after 2025, the proportion of coal in the country's total energy supply will rapidly decline. However, in 2030 the proportion of non-fossil energy in the country's primary energy supply will remain slightly lower than 20%. Highlights: Constructed a hybrid energy model with the objective of cost minimization. Simulated the change of energy system and trends of CO2 emissions in China. The CO2 emissions peak can be achieved by 2025 through evolution of energy system. Nuclear power gets developed after 2020 as a major alternative to fossil fuel. Fossil energy still accounts for more than 80% despite of rapid growth of biomass.